The Effects of Process Skill Analysis on the Teaching of Data Collecting, Processing and Interpreting - Yeany, Russell H. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
This document presents an educational research study conducted with 20 pre-service secondary science teachers to assess the effects of training in the systematic analysis of science processes on their use of strategies for teaching data collecting, processing, and interpreting. The results indicate that teaching behavior can be influenced when subjects are provided with an observation system which allows them to examine the operations and interactions which constitute a lesson. (SL)
ERIC Note: Paper presented at the annual meeting of the National Association for Research in Science Teaching (51st, Toronto, Canada, March 31 - April 2, 1978); Contains occasional light type.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Science; Educational Research; Higher Education; Observation; Preservice Teacher Education; Process Education; Science Education; Secondary School Science; Teacher Education; Speeches/Meeting Papers